Two new species of Dibamus (Squamata: Dibamidae) from Borneo - Das, I.; Lim, Kelvin K. P. (National University of Singapore, 2003)
Two new species of Dibamus are described from Sabah, east Malaysia (Borneo), one each from the highlands of Mendolong, Sipitang District, and the other from the lowland rainforests of Danum Valley, Lahad Datu District. The new highland species from Mendolong, Dibamus ingeri, differs from all congeneric species in the following combination of characters: SVL 96.0 mm; body relatively stout, body width 4.7% SVL, postoculars two; midbody scale rows 20; subcaudals 36; frontonasal divided; incomplete rostral sutures, preanal pores absent; nuchal collar starts from back of head, and relatively short tail (14.8% SVL). The new lowland species from Danum Valley, Dibamus vorisi, differs from all congeneric species in the following combination of characters: SVL to 90.1 mm; body relatively slender, body width 3.9% SVL, postoculars two; midbody scale rows 20; subcaudals 33 in a male, 11 in a female; frontonasal entire; nasal suture complete; labial suture absent; preanal pores absent; nuchal collar absent; pale body band situated in the anterior half of body, and a relatively short tail (14.2% SVL in a male; 6.1% SVL in a female).